Electrochemically switchable polymerization from surface-anchored molecular catalysts. Issue 26 (8th June 2021) - Qi, Miao; Zhang, Haochuan; Dong, Qi; Li, Jingyi; Musgrave, Rebecca A.; Zhao, Yanyan; Dulock, Nicholas; Wang, Dunwei; Byers, Jeffery A.
Abstract : Patterns of multiple polymer brushes on surfaces are obtained through application of an electrical potential to a surface functionalized with redox-switchable polymerization catalysts. Abstract : Redox-switchable polymerizations of lactide and epoxides were extended to the solid state by anchoring an iron-based polymerization catalyst to TiO2 nanoparticles. The reactivity of the molecular complexes and their redox-switching characteristics were maintained in the solid-state. These properties resulted in surface-initiated polymerization reactions that produced polymer brushes whose chemical composition is dictated by the oxidation state of the iron-based complex. Depositing the catalyst-functionalized TiO2 nanoparticles on fluorine-doped tin oxide resulted in an electrically addressable surface that could be used to demonstrate spatial control in redox-switchable polymerization reactions. By using a substrate that contained two electrically isolated domains wherein one domain was exposed to an oxidizing potential, patterns of surface-bound polyesters and polyethers were accessible through sequential application of lactide and cyclohexene oxide. The differentially functionalized surfaces demonstrated distinct physical properties that illustrated the promise for using the method to pattern surfaces with multiple, chemically distinct polymer brushes.